2012
DOI: 10.1002/ppul.22661
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory health outcomes 1 year after admission with severe lower respiratory tract infection

Abstract: Severe lower respiratory infection (LRI) is believed to be one precursor of protracted bacterial bronchitis, chronic moist cough (CMC), and chronic suppurative lung disease. The aim of this study was to determine and to describe the presence of respiratory morbidity in young children 1 year after being hospitalized with a severe LRI. Children aged less than 2 years admitted from August 1, 2007 to December 23, 2007 already enrolled in a prospective epidemiology study (n = 394) were included in this second study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 40 publications
1
48
0
Order By: Relevance
“…21 In New Zealand, hospitalised ALRI rates in children aged <2 years are 103/1,000 nationally but reach 177/1,000 in South Auckland Māori and Pacifica children. 22 These higher rates in indigenous populations in affluent countries compared to developing countries is likely related to the invariably better data collection in affluent countries.…”
Section: Epidemiology and Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…21 In New Zealand, hospitalised ALRI rates in children aged <2 years are 103/1,000 nationally but reach 177/1,000 in South Auckland Māori and Pacifica children. 22 These higher rates in indigenous populations in affluent countries compared to developing countries is likely related to the invariably better data collection in affluent countries.…”
Section: Epidemiology and Contextmentioning
confidence: 99%
“…22,35 Obtaining accurate prevalence figures on bacteria pneumonia is problematic as differentiating bacterial from viral or mixed-cause pneumonia is difficult. Even the use of WHO-defined radiological pneumonia (end-point consolidation (EPC)) is fraught with problems especially in the clinical context.…”
Section: Pneumoniamentioning
confidence: 99%
See 1 more Smart Citation
“…Recently an excellent follow-up study by Trenholme et al found that 74% of children post-hospitalisation for a severe LRTI either had a chronic moist cough, abnormal auscultatory chest sounds or abnormal chest radiograph 1 year later [8].…”
Section: Introductionmentioning
confidence: 99%
“…diagnosis or treatment) beyond the stated time points. A later study conducted in New Zealand however found that 74% of children <2 years of age had a history of chronic moist cough, moist cough or crackles and/or an abnormal chest x-ray 10–14 months after admission with severe lower respiratory tract infection [16]. Furthermore, there are no data detailing the types of ARIs that children present with in which a pre-existing chronic cough may be overlooked.…”
Section: Introductionmentioning
confidence: 99%